High-oil-absorption and high-dispersion white carbon black, preparation method thereof and application of white carbon black in rubber

CN119371721AInactive Publication Date: 2025-01-28FOSHAN SHUNDE JINCHUN SILICON MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411456772.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure BDA0005090689690000031
    Figure BDA0005090689690000031
  • Figure BDA0005090689690000091
    Figure BDA0005090689690000091
Patent Text Reader

Abstract

The invention provides high-oil-absorption and high-dispersion white carbon black and a preparation method and application thereof in rubber, and the preparation method of the white carbon black comprises the following steps: adding a silane coupling agent containing crown ether into a sodium silicate diluted solution, adding a sulfuric acid solution at 40-60 DEG C, stirring to react until the pH is 6-9, and curing at constant temperature to obtain a solution A; diluting the solution A with water, adding a sodium silicate diluted solution and a sulfuric acid solution at the same time under the condition of 70-90 DEG C, stirring to react until the pH value is 6-9, stopping adding the sodium silicate diluted solution, continuing adding the sulfuric acid solution until the pH value is 4-5.5, and aging at constant temperature to obtain a solution B; and carrying out solid-liquid separation on the solution B, washing, pulping, and carrying out spray drying to obtain the high-oil-absorption and high-dispersion white carbon black. When the precipitation-method white carbon black is prepared by adopting a two-step precipitation method, the crown ether-containing silane coupling agent is added to play a dispersion role, and the white carbon black with high oil absorption value and high dispersity is prepared and is expected to be applied to high-end rubber products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of white carbon black, and in particular to a high-oil-absorbing and highly-dispersed white carbon black and a preparation method thereof and application thereof in rubber. Background Art

[0002] Precipitated silica, also known as precipitated hydrated silica, has a molecular formula of SiO2·nH2O. It is one of the chemically synthesized amorphous silica products. It is a white powder with the main component of silica. It is insoluble in water and acid. It becomes aggregated fine particles after absorbing water. It can be dissolved in sodium hydroxide and hydrofluoric acid when heated, and is stable to other chemicals. It is resistant to high temperatures, non-combustible and has good electrical insulation. Due to its special surface structure and unique physical and chemical properties, precipitated silica is now widely used in industrial fields including silicone rubber, coatings, feed and catalyst carriers.

[0003] As a rubber reinforcing material, precipitated silica is mainly used in shoes, tires and other light-colored rubber products. In China, the consumption of precipitated silica in rubber products accounts for as high as 81% of the total consumption of precipitated silica, of which the tire industry accounts for about 38%. As one of the main reinforcing materials for rubber, changes in the microstructure of silica, such as oil absorption value, specific surface area, particle size, pore structure, etc., have a great influence on the physical and mechanical properties of rubber.

[0004] The spatial structure of precipitated silica needs to be characterized by the oil absorption of DBP. The greater the oil absorption, the more developed the 3D network bond structure in the silica, the better the dispersibility, the stronger the interaction between the agglomerates of silica, and the better the reinforcement effect of rubber compounds. The oil absorption value, i.e., the dispersibility, of precipitated silica prepared by the existing precipitation production process is difficult to reach the ideal value that meets the requirements of rubber reinforcement performance. Therefore, the existing process needs to be improved. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a high-oil absorption and high-dispersion white carbon black, a preparation method thereof and an application in rubber. When a two-step precipitation method is used to prepare precipitated white carbon black, a crown ether-containing silane coupling agent is added to exert a dispersing effect, thereby obtaining white carbon black with high oil absorption value and high dispersibility, which is expected to be used in high-end rubber products.

[0006] The present invention provides a method for preparing highly oil-absorbent and highly dispersed white carbon black, comprising the following steps:

[0007] S1. Add a crown ether-containing silane coupling agent to a sodium silicate dilute solution, then add a sulfuric acid solution at 40-60° C., stir the reaction until the pH is 6-9, and then age at a constant temperature to obtain a solution A;

[0008] S2. After diluting solution A with water, add sodium silicate dilution solution and sulfuric acid solution at the same time at 70-90°C, stir and react until the pH is 7-10, stop adding sodium silicate dilution solution, continue adding sulfuric acid solution until the pH is 3-5, and age at constant temperature to obtain solution B;

[0009] S3, after solid-liquid separation of solution B, washing, pulping, and spray drying are performed to obtain the highly oil-absorbing and highly dispersed white carbon black.

[0010] In the present invention, based on the process of preparing white carbon black by acid precipitation method, white carbon black is obtained by gelation reaction of sulfuric acid and sodium silicate, and the reaction formula is: Na2SiO3+H2SO4→Na2SO4+H2SiO3; H2SiO3+(n-1)H2O→SiO2·nH2O; in the specific reaction process, a two-step reaction is adopted, firstly, sulfuric acid and sodium silicate are reacted at a lower temperature in the first stage to generate silicon dioxide crystal particles, and then a silane coupling agent containing a crown ether is added. The silane coupling agent containing a crown ether is hydrolyzed to generate silanol, which reacts with the silicon dioxide crystal particles. The hydroxyl groups on the surface of the daughter silicon form condensation, so that the crown ether groups are grafted on the surface of the silicon dioxide crystal particles; on the other hand, the grafted crown ether groups can be complexed with the sodium ions in the solution to form a positively charged complex structure. When sulfuric acid and sodium silicate are added for the second stage reaction, the positively charged complex structure can form electrostatic attraction with the subsequently generated negatively charged silicon dioxide, so that it can play a structural guiding role for the subsequent secondary reaction of sulfuric acid and sodium silicate, guiding the generated silicon dioxide particles to grow into a multi-level branched structure, and finally preparing white carbon black with high oil absorption value and high dispersibility.

[0011] Preferably, in step S1, the concentration of the sodium silicate dilution solution is 0.05-0.5 mol / L, and the concentration of the sulfuric acid solution is 1-3 mol / L.

[0012] Preferably, in step S1, the crown ether-containing silane coupling agent is obtained by condensing 4'-aminobenzo-15-crown-5-ether with an epoxy silane coupling agent;

[0013] Preferably, the epoxysilane coupling agent is at least one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane or 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane;

[0014] Preferably, the added amount of the crown ether-containing silane coupling agent is 0.1-2 wt % of the mass of sodium silicate.

[0015] In the present invention, the amino group of 4'-aminobenzo-15-crown-5-ether can act as an electrophilic reagent to attack the epoxy group of the epoxy silane coupling agent to cause ring opening, thereby preparing a crown ether-containing silane coupling agent. The structure of the crown ether-containing silane coupling agent is shown as follows:

[0016]

[0017] Wherein, X is a partial residue of an epoxysilane coupling agent, and R is a methylene group or an ethylene group.

[0018] Preferably, in step S1, the stirring reaction time is 45-60 min, and the constant temperature aging time is 15-30 min.

[0019] Preferably, in step S2, the amount of the sodium silicate dilution solution added is 1-2 times that of the sodium silicate dilution solution in step S1.

[0020] Preferably, in step S2, the stirring reaction time is 60-80 min, and the constant temperature aging time is 20-40 min.

[0021] Preferably, in step S2, the solid-liquid separation is performed by filter pressing, and the spray drying temperature is 400-600°C.

[0022] Preferably, the pulping process further comprises adding a modifier;

[0023] Preferably, the modifier is an organic amine, preferably an aliphatic amine containing 5-20 carbon atoms, and more preferably at least one of pentylamine, hexylamine, heptylamine, octylamine, nonylamine or decylamine.

[0024] In the present invention, an organic amine modifier is added during the pulping process, and the crown ether group grafted in the white carbon black can form an inclusion complex with the amino group in the organic amine, and the alkyl chain group in the organic amine is equivalent to being grafted on the surface of the white carbon black, so that the hydrophobicity of the surface of the white carbon black can be improved, thereby further improving the dispersibility of the white carbon black, and making the interaction between the white carbon black and the non-polar rubber polymer stronger, while the compatibility and cross-linking of the two are enhanced, and the reinforcement effect is also significantly improved.

[0025] The present invention also provides a high-oil-absorbing and highly-dispersible white carbon black, which is prepared by the above-mentioned preparation method.

[0026] The present invention also provides an application of the highly oil-absorbing and highly dispersed white carbon black in rubber.

[0027] Beneficial effects:

[0028] The present invention adopts a two-step precipitation method to prepare high oil absorption, high specific surface area, and high dispersion precipitation method white carbon black. First, the first stage precipitation reaction is carried out at a relatively low temperature, and a silane coupling agent containing a crown ether is added to the precipitation reaction of the first stage, and then the second stage precipitation reaction is continued after the temperature is raised. The principle is: first, the first stage reaction is carried out at an appropriate temperature to generate and grow silica nuclei, and at the same time, a silane coupling agent containing a crown ether is added to make the crown ether group grafted on the surface of the silica nucleus, and then the second stage precipitation reaction is carried out at a higher temperature. This stage is a process in which the white carbon black nucleus continues to grow and the particles in the reaction system collide to continue to form secondary particles and tertiary particles. At this time, the grafted crown ether group is complexed with the sodium ions in the solution to form a crown ether complex, which can play a structural guiding role in the formation process of secondary particles and tertiary particles, and guide the generated silica particles to grow into a multi-level branched structure, and finally prepare white carbon black with high oil absorption value and high dispersibility, which can be effectively used in high-end rubber products. DETAILED DESCRIPTION

[0029] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0030] Example 1

[0031] A method for preparing highly oil-absorbent and highly dispersed white carbon black comprises the following steps:

[0032] (1) diluting a sodium silicate solution having a concentration of 1 mol / L with distilled water to a concentration of 0.2 mol / L, and stirring to obtain a sodium silicate dilute solution; adding a crown ether-containing silane coupling agent in an amount of 0.8 wt% by mass of the sodium silicate to 100 parts by volume of the sodium silicate dilute solution at 50° C., stirring to mix, and then dripping a sulfuric acid solution having a concentration of 2 mol / L, stirring to react for 50 minutes until the pH value is 8, and aging at a constant temperature for 20 minutes to obtain a solution A;

[0033] The crown ether-containing silane coupling agent is prepared by the following method: 4'-aminobenzo-15-crown-5-ether and 3-(2,3-epoxypropoxy)propyltrimethoxysilane are added to ethanol at a molar ratio of 1:1.2, stirred at 50°C for 3 hours, and concentrated to obtain the crown ether-containing silane coupling agent;

[0034] (2) Solution A was diluted to 3 times its volume with distilled water, and then 120 parts by volume of a 0.2 mol / L sodium silicate dilution solution and a 2 mol / L sulfuric acid solution were simultaneously added dropwise at 80° C. The mixture was stirred for 70 min until the pH reached 8.5, and then a 2 mol / L sulfuric acid solution was continuously added dropwise until the pH reached 4. After constant temperature aging for 30 min, a solution B was obtained.

[0035] (3) Pumping solution B into a plate and frame filter press for filter pressing and washing until the conductivity of the washing water is less than 0.5 mS / cm, and then conveying the obtained concentrated slurry to a pulping tank for high-speed pulping. The obtained slurry is spray-dried at 500° C. to obtain the highly oil-absorbent and highly dispersed silica.

[0036] Example 2

[0037] A method for preparing highly oil-absorbent and highly dispersed white carbon black comprises the following steps:

[0038] (1) diluting a sodium silicate solution having a concentration of 1 mol / L with distilled water to a concentration of 0.05 mol / L, and stirring to obtain a sodium silicate dilute solution; adding a crown ether-containing silane coupling agent in an amount of 2 wt% by mass of the sodium silicate to 100 parts by volume of the sodium silicate dilute solution at 60° C., stirring to mix, and then dripping a sulfuric acid solution having a concentration of 1 mol / L, stirring to react for 60 minutes until the pH value is 7, and aging at a constant temperature for 15 minutes to obtain a solution A;

[0039] The crown ether-containing silane coupling agent is prepared by the following method: 4'-aminobenzo-15-crown-5-ether and 3-(2,3-epoxypropoxy)propyltrimethoxysilane are added to ethanol at a molar ratio of 1:1.2, stirred at 50°C for 3 hours, and concentrated to obtain the crown ether-containing silane coupling agent;

[0040] (2) Solution A was diluted to 3 times its volume with distilled water, and then 100 parts by volume of a 0.05 mol / L sodium silicate dilution solution and a 1 mol / L sulfuric acid solution were simultaneously added dropwise at 70° C. The mixture was stirred for 60 min until the pH reached 8, and then a 1 mol / L sulfuric acid solution was continuously added dropwise until the pH reached 4. After constant temperature aging for 40 min, a solution B was obtained;

[0041] (3) Pumping solution B into a plate and frame filter press for filter pressing and washing until the conductivity of the washing water is less than 0.5 mS / cm, and then conveying the obtained concentrated slurry to a pulping tank for high-speed pulping. The obtained slurry is spray-dried at 400° C. to obtain the highly oil-absorbent and highly dispersed silica.

[0042] Example 3

[0043] A method for preparing highly oil-absorbent and highly dispersed white carbon black comprises the following steps:

[0044] (1) diluting a sodium silicate solution having a concentration of 1 mol / L with distilled water to a concentration of 0.5 mol / L, and stirring to obtain a sodium silicate dilute solution; adding a crown ether-containing silane coupling agent in an amount of 0.1 wt% by mass of the sodium silicate to 100 parts by volume of the sodium silicate dilute solution at 40° C., stirring to mix, and then dripping a sulfuric acid solution having a concentration of 3 mol / L, stirring to react for 45 minutes until the pH value is 8, and aging at a constant temperature for 30 minutes to obtain a solution A;

[0045] The crown ether-containing silane coupling agent is prepared by the following method: 4'-aminobenzo-15-crown-5-ether and 3-(2,3-epoxypropoxy)propyltrimethoxysilane are added to ethanol at a molar ratio of 1:1.2, stirred at 50°C for 3 hours, and concentrated to obtain the crown ether-containing silane coupling agent;

[0046] (2) Solution A was diluted to 3 times its volume with distilled water, and then 150 parts by volume of a 0.5 mol / L sodium silicate dilute solution and a 3 mol / L sulfuric acid solution were simultaneously added dropwise at 90° C. The mixture was stirred for 80 min until the pH value reached 9, and then a 3 mol / L sulfuric acid solution was continuously added dropwise until the pH value reached 4. After constant temperature aging for 20 min, a solution B was obtained;

[0047] (3) Pumping solution B into a plate and frame filter press for filter pressing and washing until the conductivity of the washing water is less than 0.5 mS / cm, and then conveying the obtained concentrated slurry to a pulping tank for high-speed pulping. The obtained slurry is spray-dried at 600° C. to obtain the highly oil-absorbent and highly dispersed silica.

[0048] Example 4

[0049] A method for preparing highly oil-absorbent and highly dispersed white carbon black comprises the following steps:

[0050] (1) diluting a sodium silicate solution having a concentration of 1 mol / L with distilled water to a concentration of 0.2 mol / L, and stirring to obtain a sodium silicate dilute solution; adding 0.8 wt% of the crown ether-containing silane coupling agent by mass of the aforementioned sodium silicate to 100 parts by volume of the sodium silicate dilute solution at 50° C., stirring to mix, and then dripping a sulfuric acid solution having a concentration of 2 mol / L, stirring to react for 50 minutes until the pH value is 8, and aging at a constant temperature for 20 minutes to obtain a solution A;

[0051] The crown ether-containing silane coupling agent is prepared by the following method: 4'-aminobenzo-15-crown-5-ether and 3-(2,3-epoxypropoxy)propyltrimethoxysilane are added to ethanol at a molar ratio of 1:1.2, stirred at 50°C for 3h, and concentrated to obtain the crown ether-containing silane coupling agent;

[0052] (2) Solution A was diluted to 3 times its volume with distilled water, and then 120 parts by volume of a 0.2 mol / L sodium silicate dilution solution and a 2 mol / L sulfuric acid solution were simultaneously added dropwise at 80° C. The mixture was stirred for 70 min until the pH reached 8.5, and then a 2 mol / L sulfuric acid solution was continuously added dropwise until the pH reached 4. After constant temperature aging for 30 min, a solution B was obtained.

[0053] (3) Solution B is pumped into a plate and frame filter press for filter pressing and washing until the conductivity of the washing water is less than 0.5 mS / cm, and the concentrated slurry is then conveyed to a pulping tank for high-speed pulping, wherein an anhydrous ethanol solution of octylamine containing 1.5 wt% of the mass of the sodium silicate obtained in step (1) is added. The obtained slurry is spray-dried at 500° C. to obtain the highly oil-absorbent and highly dispersed white carbon black.

[0054] Comparative Example 1

[0055] A method for preparing white carbon black comprises the following steps:

[0056] (1) diluting a sodium silicate solution with a concentration of 1 mol / L with distilled water to a concentration of 0.2 mol / L, and stirring to obtain a sodium silicate diluted solution; adding a sulfuric acid solution with a concentration of 2 mol / L dropwise to 100 parts by volume of the sodium silicate diluted solution at 50° C., stirring for 50 minutes until the pH value is 8, and aging at a constant temperature for 20 minutes to obtain a solution A;

[0057] (2) Solution A was diluted to 3 times its volume with distilled water, and then 120 parts by volume of a 0.2 mol / L sodium silicate dilution solution and a 2 mol / L sulfuric acid solution were simultaneously added dropwise at 80° C. The mixture was stirred for 70 min until the pH reached 8.5, and then a 2 mol / L sulfuric acid solution was continuously added dropwise until the pH reached 4. After constant temperature aging for 30 min, a solution B was obtained.

[0058] (3) Pumping solution B into a plate and frame filter press for filter pressing and washing until the conductivity of the washing water is less than 0.5 mS / cm, and then conveying the obtained concentrated slurry to a pulping tank for high-speed pulping. The obtained slurry is spray-dried at 500° C. to obtain the white carbon black.

[0059] Performance Test:

[0060] The specific surface area (BET) of the precipitated silica obtained in the above examples and comparative examples was measured according to GB / T3073-1999 "Determination of the specific surface area of ​​precipitated hydrated silica by nitrogen adsorption method"; the oil absorption value (DBP) of the precipitated silica was measured according to GB / T3072-2008 "Determination of the oil absorption value of dibutyl phthalate (DB) of precipitated hydrated silica"; the rubber was processed according to HG / T2404-2008 "Identification of precipitated hydrated silica in styrene-butadiene rubber", and the stress-strain characteristics were tested according to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; the Mooney viscosity was tested according to GB / T1232 "Unvulcanized rubber-Determination by disc shear viscometer-Part I: Determination of Mooney viscosity".

[0061] Table 1 Performance test results of the white carbon black described in the examples and comparative examples

[0062]

[0063] As shown in the results in Table 1, the white carbon black of the present invention has a high oil absorption value and high dispersibility. From the comparison between Example 1 and Comparative Example 1, it can be seen that after the crown ether-containing silane coupling agent exerts a dispersing effect, the obtained white carbon black has good compatibility with rubber, low Mooney viscosity, and greatly improved mechanical properties of tensile strength and elongation at break.

[0064] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing high oil absorption and high dispersion white carbon black, characterized in that: The steps include: S1. Add a crown ether-containing silane coupling agent to a sodium silicate dilute solution, then add a sulfuric acid solution at 40-60° C., stir the reaction until the pH is 6-9, and then age at a constant temperature to obtain a solution A; S2. After diluting solution A with water, add sodium silicate dilution solution and sulfuric acid solution at the same time at 70-90°C, stir and react until the pH is 7-10, stop adding sodium silicate dilution solution, continue adding sulfuric acid solution until the pH is 3-5, and age at constant temperature to obtain solution B; S3, after solid-liquid separation of solution B, washing, pulping, and spray drying are performed to obtain the highly oil-absorbing and highly dispersed white carbon black.

2. The method for preparing highly oil-absorbent and highly dispersed white carbon black according to claim 1, characterized in that: In step S1, the concentration of the sodium silicate dilution solution is 0.05-0.5 mol / L, and the concentration of the sulfuric acid solution is 1-3 mol / L.

3. The method for preparing highly oil-absorbent and highly dispersed white carbon black according to claim 1 or 2, characterized in that: In step S1, the crown ether-containing silane coupling agent is obtained by condensing 4'-aminobenzo-15-crown-5-ether with an epoxy silane coupling agent; Preferably, the epoxysilane coupling agent is at least one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane or 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; Preferably, the added amount of the crown ether-containing silane coupling agent is 0.1-2 wt % of the mass of sodium silicate.

4. The method for preparing highly oil-absorbent and highly dispersed white carbon black according to any one of claims 1 to 3, characterized in that: In step S1, the stirring reaction time is 45-60 minutes, and the constant temperature aging time is 15-30 minutes.

5. The method for preparing highly oil-absorbent and highly dispersed white carbon black according to any one of claims 1 to 4, characterized in that: In step S2, the amount of the sodium silicate dilution solution added is 1-2 times that of the sodium silicate dilution solution in step S1.

6. The method for preparing highly oil-absorbent and highly dispersed white carbon black according to any one of claims 1 to 5, characterized in that: In step S2, the stirring reaction time is 60-80 minutes, and the constant temperature aging time is 20-40 minutes.

7. The method for preparing highly oil-absorbent and highly dispersed white carbon black according to any one of claims 1 to 6, characterized in that: In step S2, the solid-liquid separation is performed by filter pressing, and the spray drying temperature is 400-600°C.

8. The method for preparing highly oil-absorbent and highly dispersed white carbon black according to any one of claims 1 to 7, characterized in that: The pulping process also includes adding a modifier; Preferably, the modifier is an organic amine, preferably an aliphatic amine containing 5-20 carbon atoms, and more preferably at least one of pentylamine, hexylamine, heptylamine, octylamine, nonylamine or decylamine.

9. A highly oil-absorbing and highly dispersible white carbon black, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the highly oil-absorbing and highly dispersed white carbon black according to claim 9 in rubber.

Citation Information

Cited By

  • Silicon carbide grinding slurry based on multi-mode dispersion technology and preparation method thereof

    CN121271506A